(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Mischanchuk V. N. Diagnostics of levels of formation of musical performance, training of students of institutions of art with the usage of suggestive technologies. In the article we discuss the basic steps of diagnostics of levels of formation of musical performance, training of future music teachers with the help of suggestive technologies. The state of formation of intensional system of usage of suggestive technologies in musical performance training of students of institutions of art in compliance with developed criteria and indicators is cleared up.